Missing you [large type] - Coben, Harlan, 1962- (Thorndike Press large print core series., 2014)
It's a profile, like all the others on the online dating site. But as NYPD Detective Kat Donovan focuses on the accompanying picture, she feels her whole world explode, as emotions she's ignored for decades come crashing down on her. Staring back at her is her ex-fiancé Jeff, the man who shattered her heart-- and who she hasn't seen in 18 years. Kat feels a spark, wondering if this might be the moment when past tragedies recede and a new world opens up to her. But when she reaches out to the man in the profile, her reawakened hope quickly darkens into suspicion and then terror as an unspeakable conspiracy comes to light, in which monsters prey upon the most vulnerable. As the body count mounts and Kat's hope for a second chance with Jeff grows more and more elusive, she is consumed by an investigation that challenges her feelings about everyone she ever loved-- her former fiancé, her mother, and even her father, whose cruel murder so long ago has never been fully explained. With lives on the line, including her own, Kat must venture deeper into the darkness than she ever has before, and discover if she has the strength to survive what she finds there.